DMT Models the Near-Death Experience - Timmermann, Christopher; Roseman, Leor; Williams, Luke; Erritzoe, David; Martial, Charlotte; Cassol, Héléna; Laureys, Steven; Nutt, David; Carhart-Harris, Robin (Frontiers in Psychology, 2018)
Near-death experiences (NDEs) are complex subjective experiences, which have been previously associated to the psychedelic experience and more specifically to the experience induced by the potent serotonergic, N,N-Dimethyltryptamine (DMT). Potenital similarities between both subjective states have been noted previously, including the subjective feeling of transcending one’s body and entering an alternative realm, perceiving and communicating with sentient ‘entities’ and themes related to death and dying. In this within-subjects placebo-controled study we aimed to test the similarities between the DMT state and NDEs, by administering DMT and placebo to 13 healthy participants, who then completed a validated and widely used measure of NDEs. Results revealed significant increases in phenomenological features associated to the NDE, following DMT administration compared to placebo. Also, we found significant relationships between the NDE scores and DMT-induced ego-dissolution and mystical-type experiences, as well as a significant association between NDE scores with personality trait ‘absorption’ and delusional ideation measured at baseline. Furthermore, we found a significant overlap in nearly all of the NDE phenomenological features when comparing DMT-induced NDEs with a matched group of ‘actual’ NDE experiencers. These results reveal a striking similarity between these states that warrants further investigation.